Experimental and Numerical Investigation of Clinched Joints - Jónás, Szabolcs; Tisza, Miklós (International Journal of Engineering and Management Sciences, 2018)
In this study DP600 type of steel sheets were examined by experimental and numerical simulations. The clinch joint is can be created between thin sheets with a punching tool and a die during plastic deformation. The punching tool is deforming the sheets with a given force. The process is kind of a press forming joining technique which makes the joints defines by the tools. During the process the sheets are plastically deformed and the specific “S” shaped undercut is formed. This shape is one of the most essential geometrical parameter of the joints.